POLA PEMBIBITAN UNTUK MENDUKUNG PENGEMBANGAN KLASTER SAPI POTONG DALAM RANGKA KECUKUPAN DAGING DI JAWA TENGAH - Muhson Muhson; Rachman Djamal; Eny Hari Widowati; Singgih Februhardi (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2011)
The purpose of this study is to analyze about, population growth and beef cattle, associated with (1) beef needs, (2) management and breeding patterns of beef cattle as an effort to provide seed beef cattle and cluster formation, (3) the development of breeding beef cattle to support the provision of seeds and beef, (4) strategy and direction of the formation of clusters of beef cattle breeding based on local resources. Conclusive research is a type (non experimental). Research carried out for 5 months, from March until July 2010. Research location in Grobogan District, District Sokoharjo, and Kebumen. The number of respondents by 60 people. The results showed that the value of LQ (Location quetions) are based on Gross Regional Domestic Product by 1.53 (L / Q> 1) and carrying capacity, then the cattle breeding business in Central Java is still potential for development that is equivalent to 4,968,175 animal unit . On the other hand in 2010 a new Central Java could produce 269,203 doses of frozen semen (20.17%) to support the breeding of beef cattle, the cattle population of 762 625 cows with a value of S/C 1.75. still lacking. Meanwhile, cattle breeding system Vilage Breeding Centre (VBC) to apply the system of communal house. VBC is not caused by developing, among others: the location of the house away from the residence geroup members. The calculation result breeding business for 6 years with 4 times the lambing for maintenance 3 tail stem: namely Grobogan District Net BCR (1.6> 0); NPV (USD 13,201,724> 0), IRR (69.76> 12%-SBI) ; in Sukoharjo Net BCR (1.6> 0), NPV (USD 9,111,743> 0), IRR (105.04> 12%-SBI), and in Kebumen Net BCR (1.5> 0), NPV ( USD 10,632,193> 0), IRR (76.32> 12%-SBI), a beef cattle breeding business economics at the study sites worthy developed. Factors that influence the success of beef cattle breeding business in Central Java, namely: the skills of farmers, business capital, house systems, the frequency of coaching, working area inseminator, hay production, grass production, grass production and the number of superior officers inseminator.